Forestry Administration of Cambodia : The Forest Concession Management and Control Pilot Project - World Bank (Washington, DC, 2012)
The Forest Concession Management and Control Pilot Project (FCMCPP) overall objective was developed in the early 2000s and aims at 'testing and demonstrating, through implementation, a comprehensive set of forest planning and management guidelines and control procedures and establishing an effective forest management compliance monitoring and enforcement capability'. According to the planning handbook a separate and specific document was supposed to be prepared with regard to the social issues of the forest concession planning process in order to complete the planning process. The purpose of this document is clearly for the benefit and use of forestry administration agents, concessionaires' staff, local communities and all other stakeholders who will be involved in any kind of forest management planning process in Cambodia. It is hoped that this manual will help to improve the relationship between all the forest stakeholders, and consequently help to decrease conflicts and forest destruction and to strengthen a sustainable management of the Cambodian forests.